2013
DOI: 10.1088/0004-6256/146/6/144
|View full text |Cite
|
Sign up to set email alerts
|

THE STAR FORMATION HISTORY OF THE VERY METAL-POOR BLUE COMPACT DWARF I Zw 18 FROMHST/ACS DATA

Abstract: We have derived the star formation history (SFH) of the blue compact dwarf galaxy I Zw 18 through comparison of deep HST/ACS data with synthetic color-magnitude diagrams (CMDs). A statistical analysis was implemented for the identification of the best-fit SFH and relative uncertainties. We confirm that I Zw 18 is not a truly young galaxy, having started forming stars earlier than ∼1 Gyr ago, and possibly at epochs as old as a Hubble time. In I Zw 18's main body we infer a lower limit of ≈2 × 10 6 M for the mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 52 publications
(91 reference statements)
7
46
0
3
Order By: Relevance
“…We obtain aperturecorrected stellar masses 10 7.34 M⊙ and 10 6.30 M⊙ for the NW and SE components, respectively. The total stellar mass of the I Zw 18 main body derived by SED fitting is therefore 10 7.38 M⊙, consistent with the lower limit derived by Annibali et al (2013) from the CMD.…”
Section: Comparison With I Zw 18supporting
confidence: 84%
See 1 more Smart Citation
“…We obtain aperturecorrected stellar masses 10 7.34 M⊙ and 10 6.30 M⊙ for the NW and SE components, respectively. The total stellar mass of the I Zw 18 main body derived by SED fitting is therefore 10 7.38 M⊙, consistent with the lower limit derived by Annibali et al (2013) from the CMD.…”
Section: Comparison With I Zw 18supporting
confidence: 84%
“…This SFG has been selected because its stellar mass can be determined by at least another indepen-dent method. Annibali et al (2013) have used the CMD of its resolved stellar populations to derive a stellar mass of >10 7.24 M⊙ of its main body, adopting a distance of 18.2 Mpc (Aloisi et al 2007). This is to be compared with the stellar mass obtained from the SED fitting described above.…”
Section: Comparison With I Zw 18mentioning
confidence: 99%
“…I Zw 18 is one of the lowest metallicity local galaxies (Searle & Sargent 1972;Izotov et al 2009). Our estimates for supernovae clearing in Kiso 5639 are consistent with similar conclusions about star formation in I Zw 18 based on HST WFPC2 images (Hunter & Thronson 1995;Annibali et al 2013;Lebouteiller et al 2013).…”
supporting
confidence: 90%
“…the blue supergiants. A similar problem was found for another very low-metallicity dwarf galaxy, I Zw 18, for which we derived the SFH (Annibali et al 2013). As already discussed in that study, possible explanations for the observed discrepancy are: i) the completeness behavior with magnitude is not properly taken into account, because of the severe crowding of this central region; ii) some of the most luminous blue stars in the CMD are not actually single objects but blends of two or more blue stars; iii) the timescales for the evolution of massive stars in the brightest post-MS phase are not properly modeled.…”
Section: Basis Functionssupporting
confidence: 79%
“…It is important to notice that at distances of few Mpc the SFH older than 1 Gyr necessarily relies on RGB stars, therefore the corresponding uncertainties are huge (see Appendix B of Weisz et al 2011). Together with the mentioned NGC 1569 (Greggio et al 1998;Angeretti et al 2005) and NGC 1705 (Annibali et al 2003(Annibali et al , 2009), we include in this comparison I Zw 18 (Annibali et al 2013), I Zw 36 (Schulte-Ladbeck et al 2001 and MrK 187 (Schulte-Ladbeck et al 2000). The shown galaxies are too far away even to detect the He-burning phase of stars with ages between 0.5 and 1 Gyr, hence the resulting SFHs are rather uncertain also in that age range.…”
Section: Regionmentioning
confidence: 99%